2011
DOI: 10.1016/j.cellsig.2011.07.008
|View full text |Cite
|
Sign up to set email alerts
|

SPARC mediates Src-induced disruption of actin cytoskeleton via inactivation of small GTPases Rho–Rac–Cdc42

Abstract: The matricellular glycoprotein Secreted Protein Acidic and Rich in Cysteine (SPARC) plays an important role in the regulation of cell adhesion and proliferation as well as in tumorigenesis and metastasis. Earlier, we reported that, in addition to its potent anti-angiogenic functions, SPARC also induces apoptosis in medulloblastoma cells, mediated by autophagy. We therefore sought to investigate the underlying molecular mechanism through which SPARC inhibits migration and invasion of Daoy medulloblastoma cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…In accordance with phalloidin results, we observed the increased expression of CAPZB and tropomyosin 4 ( TPM4 , NM_001001491) that stabilizes actin filaments and has a role in the regulation of cell morphology and cytoskeletal organization. This result agrees with Bhoopathi et al 20 that reports SPARC as an effector of Scr-induced cytoskeleton disruption in meduloblastoma cells. Our best Ingenuity Pathway Analysis gene network model showed that SPARC depletion was associated with an upregulation of CAPZB gene, involved in the regulation of cell morphology and cytoskeletal organization, 21 and TUBB2B , a major component of microtubules.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with phalloidin results, we observed the increased expression of CAPZB and tropomyosin 4 ( TPM4 , NM_001001491) that stabilizes actin filaments and has a role in the regulation of cell morphology and cytoskeletal organization. This result agrees with Bhoopathi et al 20 that reports SPARC as an effector of Scr-induced cytoskeleton disruption in meduloblastoma cells. Our best Ingenuity Pathway Analysis gene network model showed that SPARC depletion was associated with an upregulation of CAPZB gene, involved in the regulation of cell morphology and cytoskeletal organization, 21 and TUBB2B , a major component of microtubules.…”
Section: Discussionsupporting
confidence: 93%
“…For example, SPARC expression is correlated with malignancy, in breast cancer [10,11], melanoma [12,13], osteosarcoma [14], glioblastoma [15], and bladder cancer [16], and has a tumor-suppressing effect in medulloblastoma [17] and ovarian cancer [18,19]. In colon cancer [20], pancreatic adenocarcinoma [21,22], and nonsmall cell lung cancer [23], stromal SPARC expression is related with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Both molecules display similar tumor type specific influences on human tumor tissues [17], [70], [71], [79][82]. Both can also exert similar effects on downstream signaling pathways and molecules such as E-Cadherin [12], [83], Src [11], [84], FAK [11], [83], ERK1/2 [11], [85], MMP2 [11], [86], Akt, p53, p21 cip1/waf1 [23], [87], [88], and the Rho GTPase family members [12], [84]. Moreover, both genes have been implicated in maintenance of retinal function [5], [89], [90].…”
Section: Discussionmentioning
confidence: 99%